Glocalization in Multicultural Islamic Education Through Syi'ir Ngudi Susilo as Social Capital in the New Industrial Era - Asrori, Muhammad; Wahyuni Ahadiyah; Albab, Ulil (Academia Publication, 2026)
Indonesian education faces challenges of globalization, radicalism, and the shallowing of local identity. Multicultural Islamic education offers a solution by integrating tolerance, moderation, and cultural values. This study explores how Syi’ir Ngudi Susilo, a Javanese religious poem, can serve as social capital for multicultural Islamic education through glocalization. The Research employed a qualitative design combining library Research and fieldwork. The Research used critical discourse analysis based on Norman Fairclough’s approach, while ethnographic methods were applied to observe teaching practices in Lamongan, Gresik, and Bojonegoro. Findings reveal that Ngudi Susilo promotes moral discipline, respect for parents and teachers, and cultural pride. Its rhythmic and mnemonic style enhances student engagement and retention. Field data confirm its integration in extracurricular and religious learning, strengthening tolerance and multicultural awareness. Ngudi Susilo represents an effective glocalized educational model, fostering cultural identity while promoting moderation and inclusivity in Islamic education. Overall, this Research seeks to enhance education by exploring the theme of glocalization as a response to technological advancements, incorporating local wisdom found in Syiir Ngudi Susilo.